Construcción de una guía operativa basada en software para la gestión y control de la producción y comercialización de la asociación de productores bananeros de Ventanas Aprobaven. - Varas Beltrán, César Fabián (2014)
The need for a web application to control the work of banana crop for the Association of Banana Producers Windows "APROBAVEN" designed to the standards of the aforementioned entity. Requirements analysis is made it through information provided by the directive APROBAVEN, information was compiled by conducting surveys to people involved in the banana slang. Raised as main objective to develop software for the effective control of the operations performed in APROBAVEN , which manages the handling of agricultural work, the application supports recording work with their respective parameters, making estimation of production, access to the system only do members of the entity , there are two types of users: administrator is the user who has full access to the application , simple user only has access to the control of agricultural work , estimating, production reports. Once the supply of information to the application , it could have a highly reliable operational guide to contain all farm management activities you perform in each farm belonging has APROBAVEN . The application was completely developed in JAVA environment using the tools NetBeans IDE 7.3 , MySql 5.0 and Apache TOMCAT 7.0